ตัวนำยวดยิ่งชนิดมีเหล็กเป็นองค์ประกอบ (Fe-Based Superconductors) - ชั่งจันทร์ อาภาพงศ์ (Science Essence Journal, 2012)
ตัวนำยวดยิ่งชนิดมีเหล็กเป็นองค์ประกอบเป็นตัวนำยวดยิ่งกลุ่มล่าสุดที่มีการค้นพบในปี 2551ด้วยโครงสร้างที่มีเหล็กเป็นองค์ประกอบแสดงถึงความสัมพันธ์ของสภาพนำยวดยิ่งกับสภาวะแม่เหล็ก การมีค่าอุณหภูมิวิกฤตสูงและค่าสนามแม่เหล็กวิกฤตบนซึ่งมีค่าสูงมากทำให้ตัวนำยวดยิ่งชนิดนี้มีความ น่าสนใจทั้งในด้านสมบัติพื้นฐานและการประยุกต์ใช้งาน ในบทความนี้เรามุ่งความสนใจไปที่การค้นพบ และพัฒนาการของตัวนำยวดยิ่งชมิดมีเหล็กเป็นองค์ประกอบ รวมทั้งงานวิจัยในเชิงทฤษฎีที่พยายามจะอธิบายพฤติกรรมของสนามแม่เหล็กวิกฤตบนที่มีค่าสูงมากของตัวนำยวดยิ่งชนิดนี้ Fe-based superconductors are the recent group of superconductor discovered in 2008. The structure has an iron component that shows the relationship between superconductivity and magnetism. The discovery of Fe-based superconductors with high critical temperature values is also completely unexpected. The very high upper critical magnetic field making this superconductor attractive in terms of fundamental properties and applications. In this article, we focus on the discovery and development of Fe-based superconductors including theoretical research that explains the very high upper critical magnetic field of this material.